2002
DOI: 10.1063/1.1515133
|View full text |Cite
|
Sign up to set email alerts
|

Ge–Sn semiconductors for band-gap and lattice engineering

Abstract: We describe a class of Si-based semiconductors in the Ge1−xSnx system. Deuterium-stabilized Sn hydrides provide a low-temperature route to a broad range of highly metastable compositions and structures. Perfectly epitaxial diamond-cubic Ge1−xSnx alloys are grown directly on Si(100) and exhibit high thermal stability, superior crystallinity, and crystallographic and optical properties, such as adjustable band gaps and lattice constants. These properties are completely characterized by Rutherford backscattering,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
167
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(180 citation statements)
references
References 10 publications
12
167
1
Order By: Relevance
“…An alternative route is based on SnCl 4 , 13,14 which has the advantage of being favored in certain industrial tools. The SnD 4 precursor was initially demonstrated in combination with digermane (Ge 2 H 6 ), 1 but subsequent work has shown that trigermane (Ge 3 H 8 ) is ideally compatible with SnD 4 , 15 leading to a nearly equal incorporation efficiency for Ge and Sn. This makes it very simple to control the film composition by varying the precursor gaseous mixture.…”
Section: Synthetic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative route is based on SnCl 4 , 13,14 which has the advantage of being favored in certain industrial tools. The SnD 4 precursor was initially demonstrated in combination with digermane (Ge 2 H 6 ), 1 but subsequent work has shown that trigermane (Ge 3 H 8 ) is ideally compatible with SnD 4 , 15 leading to a nearly equal incorporation efficiency for Ge and Sn. This makes it very simple to control the film composition by varying the precursor gaseous mixture.…”
Section: Synthetic Approachmentioning
confidence: 99%
“…1 This progress is remarkable if one considers that the roomtemperature solid solubility of Sn in Ge is less than 1%. 2,3 In spite of this thermodynamic constraint, however, devicequality alloys with very high metastable Sn concentrations are now routinely synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this thermodynamics limitation, the first monocrystalline GeSn growth techniques developed were based on out of equilibrium growth conditions using ultimately low temperatures and reduced pressures. 9,10 Whereas the necessity of growing GeSn at low temperature is well understood (according to GeSn phase diagram), the necessity of using reduced pressure to enable metastable GeSn growth has never been confirmed experimentally. This letter shows metastable GeSn epitaxial growth on Ge substrate, with Sn content up to 8%, using an atmospheric pressure-chemical vapor deposition (AP-CVD) technique.…”
mentioning
confidence: 99%
“…10,13 Further anneals were then done after growth on the GeSn layers in order to assess their thermal stability. Anneals were performed in a rapid thermal anneal equipment at 400 C and 500 C for 10 and 30 min in pure N 2 .…”
mentioning
confidence: 99%
“…This concept of structural engineering via phase segregation by modifying the atomic percentage ratios of the metal layer may also be applicable to other systems with negligible solid solubility limits such as SnGe and AgGe. 12 Additionally, in the future, detailed theoretical calculations of the relevant energies and the nanoscale phase diagram of the system are needed to further shed light on the kinetics of the proposed structural nanoengineering process.…”
mentioning
confidence: 99%